PENINGKATAN BERHITUNG PERMULAAN DENGAN MEDIA MANJAMU PADA SISWA KELAS 1 TUNARUNGU DI SLB NEGERI 1 MATARAM TAHUN 2020 - Variani, Ludfia Ida (Jurnal Ilmiah Widya Pustaka Pendidikan, 2021)
This Classroom Action Research was aimed to determine: 1) the representation of the numeracy skills of the first grade deaf students, 2) the use of Manjamu media in numeracy skills especially in counting skill of the deaf students at SLB Negeri 1 Mataram in the 2019/2020 academic year. The research was conducted from August to September 2019. The research was conducted within 2 cycles and was implemented to 5 students as the object. Each cycle consists of some stages: planning, implementation, observation, and reflection. Data collection techniques used was observation which was conducted by teacher and observer, while the data analysis was carried out descriptively with percentage techniques. The success rate of students’ initial numeracy skills was classified in the categories of capable and independent, able with little guidance, quite capable with little guidance and less able with full guidance. The author collected the data on simple arithmetic skills on the aspect of operating fingers in summation and subtraction of 1-10, learning scores of numeracy skills by using research instruments. The learning scores used in this research was taken from odd semester data for the 2019/2020 academic year in the form of initial numeracy test results to map students’ initial abilities. The results of this research indicate that the use of Manjamu as the Media was proven to be able to improve the initial numeracy skills of the first-grade deaf students at SLB Negeri 1 Mataram. This was proved after the pre-action obtained an increase in score of the first cycle with an average value of 63. Meanwhile, Cycle II showed an increase with an average value of 77.2. In Conclusion: Manjamu Media bridges the thinking ability of the deaf children in learning the concept of counting according to the Basic Competencies of 2013 Curriculum, by using interesting and easy-to-use learning media will make the deaf children easier in learning the initial counting skills, especially in solving the summation and subtraction arithmetic operations.